The Influence Government in Supporting Small Businesses to Revitalize the Economy: The Case Studies of 220 Owners Various Small Businesses in Kurdistan Region of Iraq - Bapir, Azhi Kh. (Mitanni Journal of Humanitarian Sciences, 2023)
This study aims to examine the effectiveness of government in embrace of small businesses to further solve economic issues and discovering career opportunities as well as acquiring the financial aspect. To understand variables, this study employs a quantitative strategy and a descriptive research methodology. 220 participants made up the sample size that was determined utilizing a judgmental sampling technique. The questionnaire was created by the researcher as a means of gathering data, and it was subsequently modified, complied, and tabulated using SPSS statistical software, version 22, and Excel 2010. The focus of this study is to determine how the government may support small businesses in Kurdistan Region of Iraq in order to boost economic growth and job possibilities. The outcome of this study revealed that poor management and government regulations are the biggest barriers to the growth of small businesses. It also demonstrated that equal tax collection by the government would be a significant step towards the development of small projects in Kurdistan Region. Another important finding of this research proved that the backbone of economic recovery and job opportunities are small businesses. The last outcome of this study was that access to finance through large companies or investors and banks and familiarizing active policies for the progress of small businesses by the government will improve small enterprises in Kurdistan Region of Iraq.